Análise de uma corrente de turbidez com variação das propriedades físicas - Ruschel, Karina (2018)
The present work uses a numerical computational methodology and the concept of gravity current to determine the effect of the variable properties on a sediment flow. Through two different numerical approaches, it compares the advantages of using an ILES or DNS in order to reduce computational time and still keep physics of the problem. Four different cases are compared, with and without variable properties, totaling eight simulations. To verify the code a case (CASE 0) was simulated based on the article of cite espath13 by varying the coefficient of dynamic viscosity and the fall velocity using a DNS methodology. For CASE I, the effect of the ILES methodology was verified with the same parameters of CASE 0. Finally, to increase the concentration and the Reynolds number, CASES II and III use sediment parameters such as coal and pume in Boussinesq approach. It was observed that the effect of the variable fall velocity helps to reduce the velocity of the front and maintains more material in suspension for longer time periods, being this effect observed in experimental cases, which demonstrates the even greater approximation of numerical simulations with cases real.